O ensino dos anormaes preocupações em Coimbra e em Portugal no início do século XX - Diniz, Aires Antunes (Educar em Revista, 2004)
Coimbra, no início do Século XX, era uma cidade muito dinâmica na discussão das idéias pedagógicas. Estava nesse tempo muito bem ligada com a ciência pedagógica que se fazia por todo o mundo. Havia dois jornais pedagógicos que discutiam a profissão e a tecnologia educativa. Notava-se já a presença das idéias da Escola Nova, que estava ligada ao estudo dos desvios da normalidade psicológica. Decroly era bem conhecido e renascia entre nós uma Pedagogia Especial a partir da análise e diagnóstico das deficiências, obrigando à mudança do paradigma pedagógico. Esse processo era mais evidente no ensino dos cegos e dos surdos, mas criou ainda a necessidade social de protecção dos delinqüentes, que eram também crianças e jovens em risco moral. Tudo mostrava Portugal como um país avançado e pioneiro numa pedagogia especial. Foi o que infelizmente um novo tempo político veio obstaculizar, mas isso é já o tema de outra investigação. Abnormal education as a chief interest in Coimbra and Portugal in the beginning of the XX Century Abstract In the first years of the XX Century, Coimbra was a very dynamic town in the social and scientific discussion of pedagogical ideas. Coimbra is well linked to an already Global Education Science. In Coimbra, there were two pedagogical journals which discussed not only the teaching profession, but also pedagogical theory and educational practices. We can already see Escola Nova ideas well-linked to the psychological and sociological research about deviance to normal behaviour. Decroly was well-known among us and with him a Special Pedagogy was updated through the analysis and diagnosis of disabilities and handicaps in children and young people, leading to a new educational paradigm. The uprising of a new educational process is clear not only in education of blind and deaf children, but also in the creation of a social protection to the young people, sometimes delinquent or people with only some moral and/or criminal deviance, that are also children and young at moral risk. At that time, Portugal could be seen as a pioneer and an advanced country in Special Education. Unfortunately, a new political era is coming, putting barriers to this future. But this is another idea for a new research.